Teaching breaking bad news in a gyneco-oncological setting: a feasibility study implementing the SPIKES framework for undergraduate medical students - Cosima Zemlin; Nasenien Nourkami-Tutdibi; Pascal Schwarz; Gudrun Wagenpfeil; Sybelle Goedicke-Fritz (BMC Medical Education, 2024)
Abstract Background It is a crucial task for physicians to deliver life threatening information to patients (breaking bad news; BBN). Many aspects influence these conversations on both sides, patients, and doctors. BBN affects the patient-physician relationship, patients’ outcome, and physicians’ health. Many physicians are still untrained for this multi-facetted task and feel unprepared and overburdened when facing situations of BBN. Therefore, any faculties should aim to integrate communication skills into their medical curricula as early as possible. The SPIKES protocol is an effective framework to deliver BBN. Aim of this study is to evaluate the feasibility and obstacles of a BBN seminar and its acceptance and learning curve among undergraduate medical students. Methods 158 2nd year undergraduate medical students attended a compulsory BBN seminar. The task was to deliver a cancer diagnosis to the patient within a patient - physician role-play in a gyneco-oncological setting before and after a presentation of the SPIKES protocol by the lecturer. The students evaluated important communication skills during these role-plays respectively. Self-assessment questionnaires were obtained at the beginning and end of the seminar. Results Most students indicated that their confidence in BBN improved after the seminar (p < 0.001). They like the topic BBN to be part of lectures (76%) and electives (90%). Communication skills improved. Lecturer and seminar were positively evaluated (4.57/5). Conclusion The seminar significantly increased confidence and self-awareness in delivering life-threatening news to patients among undergraduate medical students. Important learning aspects of BBN and communication skills could be delivered successfully to the participants within a short time at low costs. The integration of communication skills should be implemented longitudinally into medical curricula starting before clinical education to increase the awareness of the importance of communication skills, to decrease anxiety, stress, and workload for future doctors and– most importantly– to the benefit of our patients.